Character Education Through Realistic Mathematics Learning Based On Ethnomathematics - Salafudin Salafudin; Muhamad Sugeng Sholahuddin; Heni Lilia Dewi; Alimatus Sholikhah (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
Mathematics is a discipline that can improve thinking skills. However, in reality, the mathematics thinking skills of elementary school students are still low. This is because the mathematics learning used is not optimal and still uses conventional learning. In the process of mathematics learning, there is an integration of character values with mathematics material. Character building through mathematics learning has not been done relatively. The current mathematical concept can be related to cultural activities called ethnomathematics. Through ethnomathematics, mathematics learning becomes more realistic. The purpose of this research is to build students’ character and improve student’s mathematic learning achievement through developing student worksheets with a mathematical approach based on ethnomathematics. The methods of the research were research and development by using steps including preliminary study, design, development, and dissemination. The result of the research is student's worksheets fulfill valid, practical, and effective criteria. The result of the validity of teaching media shows that the average number is 96 % with very good criteria. The effectiveness test shows that there is a distinction of student’s achievement before and after the treatment and the student’s achievement on average is increased. Based on the analysis of student's answers on student worksheets, four characters are built through the learning process with a realistic mathematic approach based on ethnomathematics, such as creativity, independence, curiosity, and nationality. Keywords: character building, realistic mathematics learning, ethnomathematics.